Autologous gastrointestinal reconstruction surgery for short bowel syndrome: the cornerstone for intestinal rehabilitation. Issue 2 (11th April 2022) - Gondolesi, Gabriel E.; Ortega, Mariana; Martinez, Maria I.; Rumbo, Carolina; Solar, Héctor
Abstract : Purpose of review: Intestinal failure (IF) evolved from being the last recognized organ failure, to become one of the most progressive fields in terms of therapeutic alternatives and results. Short bowel syndrome (SBS) is the main cause of IF in adults and children. The use of surgery allowed patients with unfavorable anatomy type and length to be wean off parenteral nutrition. We aim to evaluate its current impact on intestinal rehabilitation. Recent findings: Autologous gastro-intestinal reconstructive surgery (AGIRS), including bowel lengthening contributes by converting patient's anatomy to a more favorable one, improving quality of life, and modifying the natural history of the disease, allowing to recover intestinal autonomy in approximately 70% of the adults and 50% of the children's with SBS-IF. The current use of postsurgical medical rehabilitation strategies including the use of enterohormones complement the path to sufficiency, increasing the chances of success in both age group of patients. Summary: The development of AGIRS has changed the outcome of SBS-IF patients, becoming the main surgical procedure prescribed in multidisciplinary units, allowing to enhance the number of patients achieving intestinal autonomy throughout rehabilitation, leaving transplantation as the last surgical alternative.